Memanifestasi Deiksis dalam Film “Ngeri-Ngeri Sedap” Karya Bene Dion Rajagukguk: Analisis Pragmatik - Amaniyah, Dita Zuaimatul; Rumilah, Siti (GERAM: Gerakan Aktif Menulis, 2023)
This research aims to analyze the use of deixis in the film "Ngeri-Ngeri Sedap" from a pragmatic perspective. Deixis is an important aspect in linguistic studies which is related to the use of signs that refer to the context of space and time. The film text analysis method is used to identify and analyze the use of deixis in the context of situations involving characters, location, time, and interactions between characters. The research results show that the use of deixis in this film aims to create a communicative effect and build relationships between the characters and the audience, by using personal, time, place, atmosphere, and social deixis. The use of pointing signs, such as body gestures and the placement of objects in scenes, is used to clarify the spatial relationships between characters and objects in the story. Pronouns are also often used to replace previously introduced references, maintaining cohesion in the narrative. In addition, the effective use of time-telling words helps the audience understand the sequence of events and establish chronology in the story. This research provides deeper insight into the use of language in communicative situations in the context of films, as well as a contribution to the development of pragmatic theory and an understanding of the audience's experience.